2015
DOI: 10.11158/saa.20.2.1
|View full text |Cite
|
Sign up to set email alerts
|

<p class="HeadingRunIn"><strong>First record of <em>Amblyomma rotundatum</em> tick (Acari: Ixodidae) parasitizing a bird collected in Canada</strong></p>

Abstract: Migratory birds disperse engorged ticks across Canada during northward spring migration. During our tick-host study, we collected a nymphal Amblyomma rotundatum Koch, from a Veery, Catharus fuscescens (Stephens) (Passeriformes: Turdidae), at Long Point, Ontario, Canada. In the laboratory, this nymph molted to a female in 44 d. The infestation of A. rotundatum on a Veery constitutes a first tick-host record, and a new distributional record in Canada. Notably, this novel collection is the northernmost record of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In the only previous study to systematically examine northbound spring migrants for ticks immediately upon entry into the United States, Mukherjee et al (7) found that 3% of songbirds hosted a tick, some of which were infected with spotted fever group Rickettsia species. Further, Central and South American Amblyomma spe-cies have been detected on northward-migrating birds as far north as Chicago, IL, and Canada (5,6,17,18).…”
mentioning
confidence: 99%
“…In the only previous study to systematically examine northbound spring migrants for ticks immediately upon entry into the United States, Mukherjee et al (7) found that 3% of songbirds hosted a tick, some of which were infected with spotted fever group Rickettsia species. Further, Central and South American Amblyomma spe-cies have been detected on northward-migrating birds as far north as Chicago, IL, and Canada (5,6,17,18).…”
mentioning
confidence: 99%
“…In particular, migratory birds can transport ticks thousands of kilometers during transhemispheric and intercontinental migration (Hoogstraal & Kaiser 1961, Olsén et al 1995, Scott & Durden 2015a, Scott & Durden 2015b. Epidemiologically, some of these ticks are infected with tick-borne pathogens.…”
Section: Dna Barcoding Ticksmentioning
confidence: 99%
“…If it encounters a recently hatched tick egg mass, it can become heavily infested with hundreds of larvae. Because some American Kestrels are migratory, these small falcons have the potential to transport tick long distances comparable to migratory songbirds (Scott et al 2001, Morshed et al 2005, Ogden et al 2008, Scott et al 2010, Scott et al 2012, Scott 2015, Scott & Durden 2015a.…”
Section: Introductionmentioning
confidence: 99%
“…Migratory Neotropical songbirds have an inherent capacity of flying long distances in a short period of time, and reaching Canada (Scott et al 2012, Scott & Durden 2015a, Scott & Durden 2015b, Scott & Durden 2015c. This capability allows them to transmit ixodid ticks long distances while the attached ticks are taking a blood meal.…”
Section: Introductionmentioning
confidence: 99%
“…These Amblyomma spp. include: A. americanum (Linnaeus) (Scott et al 2001(Scott et al , 2010, A. humerale Koch (Morshed et al 2005), A. inornatum (Banks) (Ogden et al 2008a), A. longirostre (Koch) (Scott et al 2001(Scott et al , 2010(Scott et al , 2012, A. maculatum Koch (Scott et al 2001(Scott et al , 2010(Scott et al , 2012Ogden et al 2008a), A. rotundatum Koch (Scott & Durden 2015a), and A. sabanerae Stoll (Scott et al 2001(Scott et al , 2010(Scott et al , 2012Scott & Durden 2015b). Within the Great Lakes region, Hamer et al (2012) also reported A. nodosum Neumann, a neotropical tick from Brazil, collected from a migratory songbird at the southern end of Lake Michigan.…”
Section: Introductionmentioning
confidence: 99%